Effect of nitrogen and irrigation regimes on the yield and quality of sweet basil (Ocimum basilicum L.) - Singh, Munnu (Journal of Spices and Aromatic Crops, 2002)
Field experiments were conducted at Bangalore, to study the effect of nitrogen and irrigation reghnes on growth, herbage, yield and quality of oil of sweet basil (Ocimum basilicum L.). Application of nitrogen at 200 kg ha-1 significantly increased the plant height, plant spread, herbage and oil yield compared with control (no nitrogen). Irrigation at 0.75 IW : CPE ratio (irrigation water : cumulative pan evaporation) increased the plant spread, herbage and oil yield compared with that of 0.25 IW : CPE ratio. Oil content and quality were not influenced by nitrogen and irrigation regime. Water use efficiency (WUE) was maximum at 0.25 IW : CPE ratio (0.337 kg oil ha-1 mm-1 water used) compared with 0.75 IW : CPE ratio (0.196 kg oil ha-1 mm-1 water used). Similarly nitrogen application increased the water use efficiency compared with that of control.